1996
DOI: 10.1093/humrep/11.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Stress and stress-related hormones during in-vitro fertilization treatment

Abstract: Whether stress and infertility are linked as cause or consequence is unclear, and there is no consensus on the most appropriate methods for measuring stress in infertile women. To address this question, we measured changes in biochemical and questionnaire-based assessments of stress in infertile women. Median baseline, follicular phase and pre-operative serum prolactin (229, 311 and 457 mIU/l) cortisol (278, 369 and 496 nmol/l) and state anxiety score (38, 40 and 49) respectively all increased during stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 27 publications
3
58
1
4
Order By: Relevance
“…Stress and elevated hydrocortisone levels can also affect female fertility. One study shows that in women who underwent in vitro fertilization, baseline urine cortisol levels increased from ∼230 nM to ∼500 nM (32). According to our results, hydrocortisone blocked CatSper activation by P4 with an IC 50 of 153 nM.…”
Section: Discussionsupporting
confidence: 76%
“…Stress and elevated hydrocortisone levels can also affect female fertility. One study shows that in women who underwent in vitro fertilization, baseline urine cortisol levels increased from ∼230 nM to ∼500 nM (32). According to our results, hydrocortisone blocked CatSper activation by P4 with an IC 50 of 153 nM.…”
Section: Discussionsupporting
confidence: 76%
“…Infertility, as well as its treatment, can be considered significant chronic stressors, but the neuroendocrine components of this response and the extent to which environmental contaminants modulate this are unclear. Our results are similar to prior studies that reported no difference in IVF outcomes by cortisol levels, using urine, saliva, or serum levels in addition to self-reported stress questionnaires [13,25,26]. Yet, few prior studies employed urine cortisol as a psychological stress biomarker for IVF couples.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies employing psychometric measures, biological stress measures, or both have reported varied, and often conflicting, results for associations between psychological stress and IVF outcomes [5,13,14,[23][24][25][26]. Infertility, as well as its treatment, can be considered significant chronic stressors, but the neuroendocrine components of this response and the extent to which environmental contaminants modulate this are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on the association between an aberrant stress response and poor fertility outcomes are mixed, with studies supporting an association (1,6,8,11,12,15,17,22,(24)(25)(26), studies refuting an association (13,18,(27)(28)(29), and even a study suggesting a positive impact of stress on reproduction (14). In addition, there are studies demonstrating a negative impact of stress on male reproduction (19,30,31).…”
Section: Does Stress Negatively Impact Fertility?mentioning
confidence: 99%